2013
DOI: 10.1021/ol4008266
|View full text |Cite
|
Sign up to set email alerts
|

Novel Double [3 + 2 + 1] Heteroannulation for Forming Unprecedented Dipyrazolo-Fused 2,6-Naphthyridines

Abstract: A novel four-component strategy for the efficient synthesis of unprecedented dipyrazolo-fused 2,6-naphthyridines through a double [3 + 2+1] heteroannulation has been described. The bond-forming efficiency, accessibility, and generality of this synthesis make it highly valuable to assemble tetra-heterocyclic scaffolds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Thus, depending on the substituent in the phenyl ring of aniline, two different products were obtained. The same authors also reported a four‐component reaction of phenylglyoxal and 7 , with which dipyrazolo‐fused 2,6‐naphthyridines could be obtained through a double [3+2+1] heteroannulation reaction by using n ‐butyric acid as a catalyst …”
Section: Aliphatic Axb3 Smentioning
confidence: 97%
“…Thus, depending on the substituent in the phenyl ring of aniline, two different products were obtained. The same authors also reported a four‐component reaction of phenylglyoxal and 7 , with which dipyrazolo‐fused 2,6‐naphthyridines could be obtained through a double [3+2+1] heteroannulation reaction by using n ‐butyric acid as a catalyst …”
Section: Aliphatic Axb3 Smentioning
confidence: 97%
“…[22] On this basis, diverse nitrogencontaining heterocyclic compounds were constructed by using 5-aminopyrrole as the starting material including bicyclic, tricyclic, tetracyclic, and spiro-fused pyrazole derivatives. [23][24][25][26][27] However, the reaction of introducing ar-ylthio group on 5-aminopyrrole to synthesize unsymmetrical diaryl sulfide has rarely been reported. Numerous studies have shown that the introduction of sulfur-containing groups increased biological activity of functional molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In special, 5-amino-1 H -pyrazoles are valuable compounds that present several biological and pharmaceutical activities including antiviral, anticancer, antituberculosis, anti-inflammatory, antifungal and antidepressive activity [1417]. Moreover, they have been extensively used as synthons to prepare a wide variety of fused N-heterocycles of synthetic and pharmacological importance [1820]. Thus, an effective strategy for the design and the preparation of new pharmacologically promising drugs that combine at least two bioactive moieties in one molecule avoiding residual metal in transition-metal catalysis in environmental benign conditions is desired.…”
Section: Introductionmentioning
confidence: 99%